Assessment of symptoms and complications in treatment naive newly diagnosed type 2 diabetes mellitus and their correlation with glycemic parameters: A cross-sectional study from kalyana Karnataka - Swaraj Waddankeri; S W Meenakshi; B Mangshetty (Wolters Kluwer Medknow Publications, 2021)
Background and Objectives: The Assessment of symptoms in newly diagnosed type 2 diabetes mellitus (T2DM) and determine its correlation with glycemic parameters such as General random blood sugar (GRBS) Fasting blood sugar (FBS), Post prandial blood sugar (PPBS), and Glycated hemoglobin (HbA1c) at diagnosis. Methodology: Cross-sectional, observational, single-arm study of 73 consecutive cases of treatment naïve, newly diagnosed T2DM with a baseline HbA1c >9. Hyperglycemic symptoms and complications were assessed at diagnosis and evaluated for their association with glycemic parameters (FBS, PPBS, and HbA1c). Results: Nocturia and weight loss were positively correlated (P < 0.05) to FBS, PPBS, and HbA1c. The most frequently observed symptoms in patients with complication were weight loss (16/18, 88.9%), followed by nocturia (14/18, 77.8%), polyuria (12/18, 66.6%), and balanitis (10/18, 55.5%). Furthermore, nocturia was associated with higher GRBS and polyuria/polyphagia with higher HbA1c at diagnosis. The mean General Random Blood Sugar (GRBS) was 335.4 mg/dl. The mean FBS and PPBS were 272 mg/dl and 397.1 mg/dl, respectively. The mean of HbA1c at diagnosis was 12.6%. Conclusions: Hypertension was the most common comorbidity. Chronic kidney disease and nonproliferative diabetic retinopathy were the commonly observed complications. In newly diagnosed T2DM patients, nocturia, polyuria, and weight loss were the most common symptoms associated with higher glycemic levels at presentation. Hypertension with higher creatinine at diagnosis is one of the ominous signs of harboring one or more underlying complication.